Al-Attas dan al-Qaradawi Mengenai Islam dan Sekularisme - Suharto, Ugi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2002)
Al-Attas and al-Qaradawi share some fundamental views on the relationship between Islam and secularism. Boths scholars agree that the term "secularism" should not be arabize as ‘almaniyyah or 'ilmaniyyah; that Aristotle was the initiator of secular thinking; and that Muslim must fight against secularism seriously. As a Muslim thinker al-Attas warns the Muslims on the danger of secularism as a philosophical program and its manifestation in their individual as well as societal life. Similarly, as a Muslim jurist al-Qaradawi reminds them guard the four aspects of Islam; `aqidah, `ibadah, akhlaq and shari'ah from the evil of secularism.